Enhancing EFL Learning Through Computer-Based Gamification: An Investigation of Impact. - Mrissa, Brahim; Anasse, Khadija (International Journal of Language and Literary Studies, 2023)
This study examines the impact of computer-based gamification on English language learning among adult and young learners. In order to gauge any potential impact of this teaching technique on learners, empirical research has been conducted using a quantitative design. Relevant data was collected using two quantitative data collection instruments; a questionnaire and a proctored test. The questionnaire sought to get insights into adult learners’ perspectives with regard to web-based learning while the test measured any impact of using Kahoot on English language performance and retention. The current study showed that the use of Kahoot positively affects learners’ performance, motivation, engagement, and retention of English language skills and components. Besides, this research offers valuable recommendations to ESL teachers and designers of teaching materials as well, suggesting more integration of gamification in language teaching programs to enhance motivation and enjoyment in the EFL classroom. Furthermore, it emphasizes some advantages and drawbacks of integrating web-based gamification in teaching.